2017
DOI: 10.17113/ftb.55.01.17.4693
|View full text |Cite
|
Sign up to set email alerts
|

Three New Lactobacillus plantarum Strains in the Probiotic Toolbox against Gut Pathogen Salmonella enterica Serotype Typhimurium

Abstract: SummaryThe benefi ts of probiotic bacteria have been widely explored. However, fermented foods and digestive system of humans and animals are an inexhaustible source of new potentially probiotic microorganisms. In this study we present three new Lactobacillus plantarum strains isolated from diff erent dairy products: cow′s cheese, sheep′s cheese and whey. In order to determine the antibacterial activity of yet unexplored L. plantarum strains against Salmonella enterica serotype Typhimurium, in vitro competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…plantarum in raw milk and its low technological importance in standard milk processing. However, strains with probiotic properties have been isolated from different dairy-related niches, for example, camel milk [ 25 ], cow's or ewe's raw-milk cheeses, and whey [ 103 106 ]. Hence, recent studies are more focused on implementing probiotic strains of Lb.…”
Section: Lb Plantarum In Traditional Food Systmentioning
confidence: 99%
“…plantarum in raw milk and its low technological importance in standard milk processing. However, strains with probiotic properties have been isolated from different dairy-related niches, for example, camel milk [ 25 ], cow's or ewe's raw-milk cheeses, and whey [ 103 106 ]. Hence, recent studies are more focused on implementing probiotic strains of Lb.…”
Section: Lb Plantarum In Traditional Food Systmentioning
confidence: 99%
“…by potential probiotic LAB strains in the coculture assay [16,33,34]. In line with this, Potočnjak et al [25] reported that all the tested Lactobacillus plantarum strains (A, B, and S1) were able to inhibit (p < 0.05) the growth of Salmonella Typhimurium at all-time points (6, 12, and 24 h) in the coculture assay. e same author reported that after 24 h of cocultivation, the number of Salmonella cells was reduced 1000 times in comparison with Salmonella monoculture and the inhibition was most pronounced after 12 h of coincubation and amounted to 97, 98, and 94% by strains A, B, and S1, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…To evaluate the effect of selected potential pure strains (Lactococcus lactis E124, Lactobacillus paracasei K114 and Lactobacillus plantarum K132) and their combinations on the growth of Salmonella Typhimurium DT104, liquid coculture technique was used as described by Potočnjak et al [25] with some modifications. Before cocultivation, the selected strains and Salmonella Typhimurium DT104 were grown separately in de Man, Rogosa, and Sharpe (MRS) broth and tryptic soy broth (TSB), respectively.…”
Section: Coculture Assaymentioning
confidence: 99%
“…Although the same strains adhered to epithelial cells at high rates, their competition abilities were limited against S. Enteritidis. On the other hand, Lau and Chye [ 12 ], Potočnjak et al [ 52 ] and Feng et al [ 53 ] reported that Lactobacillus strains prevented Salmonella spp. from sticking to Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Survival of passage through the challenging conditions in the digestive tract and adhesion to human cells are important for strains to show their health effects in the human gut. The resistance to such conditions is crucial, as exposure to bile salts causes dissociation of the lipid bilayer of cell membranes and disruption of the integrity of cells [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Consumption of approximately 1.0 × 10 6 to 1.0 × 10 10 viable cells per day is generally accepted as the minimum limit required in order to gain satisfactory probiotic functions in the intestine [ 15 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%